Factibilidad para la implementación de microempresa de acopio de maíz y elaboración de alimentos balanceados en la comunidad La Sabana-Chone - Parrales Palma, Kevin Alexander (2021)
The objective of this study was to determine the feasibility for the creation of a collection of corn and the formulated feeds production micro-enterprise in the community of La Sabana-Chone, a market research was performed to know the needs and size of the market, the population of Chone was studied by a market research projected to 2020, of this population only 43,4 % was taken into consideration because this percentage is connected to the population that is dedicated to agriculture, livestock and fishing, the sample size was calculated in 382 people, reaching an acceptance of 87 % of the investigated families, which means a demand of 8 834 40kg bags / month, 29 % is allocated to feed pigs, 24 % to chickens and 37 % to heifers. In the engineering of the project, formulated feeds were elaborated, pointing out the characteristics of the parameters established by the NTE INEN 1829:2014 standard, following the ranges established by Pronaca, Unicol and the NTE INEN 2051:1995 standard, the labels were elaborated, the plant design was created with different areas, the production system was planned and the necessary equipment and tools were sought for the process. Through Leopold's matrix it was shown that the proposed project will generate positive impacts. The financial study of the project indicates that it is profitable with the NPV indicators $ 259 921, 73 and IRR, 26,16 %. In the benefit-cost, $ 0,29 is earned for every dollar invested and the product / capital ratio has a profitability of 153,02 %.